The effect of sous-vide cooking on the antioxidant properties of oyster mushroom (Pleurotus ostreatus L.) - Törős, Gréta; Prokisch, József; Peles, Ferenc; Nagy, Róbert; Nagy, János; Béni, Áron (Acta Agraria Debreceniensis, 2024)
Oyster mushrooms (Pleurotus ostreatus L.) are renowned for their antioxidant, antimicrobial, and prebiotic properties. This study explores the antioxidant characteristics, activity, and β-glucan content in freeze-dried mushroom samples, investigating the influence of sous-vide cooking. Uncooked freeze-dried P. ostreatus and three pre-cooked freeze-dried samples (70, 80, 90 °C through 4 hours) were analysed for Total Polyphenol Content (TPC), Total Flavonoid Content (TFC), Radical Scavenging (DPPH), Ferric Reducing Antioxidant Power (FRAP), and β-glucans content via HPLC and Total Dietary Fiber (TDF) via enzymatic gravimetric method. Results indicate that uncooked mushroom powder exhibited superior antioxidant capabilities compared to cooked samples. The sous-vide cooked (80 °C) mushrooms displayed the highest total phenolic and flavonoid content. Moreover, pre-cooked (70 °C) mushroom powder demonstrated the highest β-glucan content, significantly surpassing the uncooked control sample. Notably, pre-cooked groups (80, 90 °C) demonstrated significantly higher TDF levels compared to uncooked sample. This research offers valuable insights into the potential use of mushrooms as high-antioxidant, antimicrobial, and prebiotic food or feed supplements, with broad implications across various fields.